Search for New Astronomical Site in Indonesia: II. Transparency of Tropical Atmosphere - Taufiq Hidayat; Putra Mahasena; Budi Dermawan (Jurnal Matematika & Sains, 2010)
We present a theoretical model of atmospheric transparencies for tropical region of Indonesia in the framework of developing multi-wavelength astronomical observations. The wavelengths of interest are radio, infrared, and optical domains. Beside science objectives, sky transparencies are needed to determine the corresponding wavelength band to be optimized in the observatory design. A clear sky condition is then assumed in the model and a line-by-line radiative transfer code is used at high spectral resolution. Â The results, combined with study on meteorological satellite data, are utilized to provide various information to select the best possible sites for a new astronomical observatory in Indonesia.Â